Molecular screening of xerophilic Aspergillus strains producing mycophenolic acid. Issue 2 (February 2017) - Mouhamadou, Bello; Sage, Lucile; Périgon, Sophie; Séguin, Virginie; Bouchart, Valérie; Legendre, Patrick; Caillat, Mathilde; Yamouni, Hayet; Garon, David
Abstract: Mycophenolic acid (MPA) is the fungal secondary metabolite displaying several biological properties. Up to now, screening of fungal strains producing MPA has mainly been the result of the search of this molecule in their culture medium by chemical methods. Here we developed a molecular approach by targeting the expression level of the MpaC gene encoding the polyketide synthase, one of the key enzymes involved in the MPA synthesis. Thirty xerophilic Aspergillus strains were identified using the RNA polymerase II subunit and the β-tubulin genes. Seven Aspergillus species were evidenced. The expression level of the MpaC gene was quantified and compared to the MPA production rate. Only Aspergillus pseudoglaucus and all the eight strains of this species produced MPA. While the MpaC gene was not expressed or weakly expressed in the MPA non-producing strains, all the A. pseudoglaucus strains presented a high level of expression of this gene. The highest expression level of the MpaC gene among the MPA non-producing strains was significantly lower than the lowest expression level of this gene in the MPA producing strains. To our knowledge, this is the first study that demonstrates the effectiveness of molecular approach for the screening of MPA-producing species. Highlights: We investigated the mycophenolic acid (MPA) production in Aspergillus species. We found that only and all the Aspergillus pseudoglaucus strains produced MPA. The MPA production coincided with a high expression of the polyketide synthase gene. This suggests the efficiency of molecular approach to screen MPA-producing species.